If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(x + 8) = 18 + 3x Reorder the terms: -3(8 + x) = 18 + 3x (8 * -3 + x * -3) = 18 + 3x (-24 + -3x) = 18 + 3x Solving -24 + -3x = 18 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -24 + -3x + -3x = 18 + 3x + -3x Combine like terms: -3x + -3x = -6x -24 + -6x = 18 + 3x + -3x Combine like terms: 3x + -3x = 0 -24 + -6x = 18 + 0 -24 + -6x = 18 Add '24' to each side of the equation. -24 + 24 + -6x = 18 + 24 Combine like terms: -24 + 24 = 0 0 + -6x = 18 + 24 -6x = 18 + 24 Combine like terms: 18 + 24 = 42 -6x = 42 Divide each side by '-6'. x = -7 Simplifying x = -7
| 6x+7x-3x=64 | | givenf(x)=x^3 | | 4w-20= | | 2/5x=5/6 | | 3/n=1/8 | | 8s-10=10 | | 3x^2=7x-2x | | 6-(x+4)+3x=8x-2(3x+4) | | 3b/4=3/2 | | N/21=1/7 | | 2/3=1/1=f | | 2/8=n/32 | | s+5=4 | | 2a+3=a-32 | | 20x=925-20x | | 6x+14+x= | | 4(3n-5)=19 | | C/2=2/3 | | -9(x-5)=9-8x | | 2b+9=-5(b-6) | | 4n-21=-61+9n | | 3p-29=-26+4p | | (3x^2-10)=17 | | 9x^2-36x=o | | 2.4z=7.2 | | 3x5/12 | | 0.044x+x=99 | | x=-47/90 | | x-215=39 | | 17=8+y | | 4y+5+7y= | | 16-(2/x^3)=0 |